Application of E- worksheet Oriented on PBL Model to Improve Critical Thinking Skills on Acid-Base Material - Azizah, Maharani Puspita Nur; Muchlis, Muchlis (Jurnal Pijar Mipa, 2024)
Humans often interact with substances containing acids and bases daily. Learning in schools in grade XI, namely in phase F, one of the element achievements that students must complete is that students can use the concept of acids and bases in everyday life. Students are expected to have critical thinking and open minds through scientific work increasingly and, at the same time, strengthen the profile of Pancasila students, especially honest, objective, critical reasoning, creative, independent, innovative, collaborative, and globally diverse. The objective of the research will be to enhance students' critical thinking ability in E-worksheet learning-oriented Problem-Based Learning models within the subject matter of acid and base. The research design used is a descriptive quantitative approach with a pre-experimental design using a "Pretest-Posttest Control Group design ". The sample used in this research was 36 students in two classes XI of SMAN 1 Waru, Sidoarjo City. Data were collected using observation sheets, tests, and questionnaires. Two lecturers and a chemistry teacher validated the instruments to collect data. Data analysis used N-Gain to explain how much students' critical thinking skills increased. It was found that students' critical thinking skills increased significantly, with 63,9% of students in class XI-1 and 83,3% in class XI-5 obtaining N-Gain scores included in the high category, which falls into a high category. The results of the study confirm that E-worksheets oriented towards PBL are effective in developing critical thinking skills in chemistry among students, especially on the topic of acids and bases.